New small-size peptides possessing antifungal activity - Garibotto, Francisco Matías (2010)
The synthesis, in vitro evaluation, and conformational study of a new series of small-size peptides acting as antifungal agents are reported. In a first step of our study we performed a conformational analysis using Molecular Mechanics calculations. The electronic study was carried out using Molecular electrostatic potentials (MEPs) obtained from RHF/6-31G calculations. On the basis of the theoretical predictions three small-size peptides, RQWKKWWQWRR-NH2, RQIRRWWQWRR-NH2, and RQIRRWWQW-NH2 were synthesized and tested. These peptides displayed a significant antifungal activity against human pathogenic strains including Candida albicans and Cryptococcus neoformans. Our experimental and theoretical results allow the identification of a topographical template which can serve as a guide for the design of new compounds with antifungal properties for potential therapeutic applications against these pathogenic fungi.